Constitutional rules, reputation, and sovereign debt - Rowlands, Dane (1993)
Examines the possibility of creating constitutional rules which can support sovereign debt contracts which would otherwise violate the requirement of time-consistency. Looks at the possibility of establishing international reputation with internal enforcement mechanisms.